2014
DOI: 10.1111/eea.12163
|View full text |Cite
|
Sign up to set email alerts
|

Stay cool, travel far: cold‐acclimated oriental fruit moth females have enhanced flight performance but lay fewer eggs

Abstract: Acclimation to a particular environment may provide organisms with advantages in that environment. In species with multiple generations per year, acclimation may cause life-history traits to vary with season and between generations. We investigated flight performance, lifetime egg production, and longevity in relation to the temperature experienced during development and adulthood in the invasive moth pest Grapholita molesta (Busck) (Lepidoptera: Tortricidae). We found that females that developed at low temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
11
2
Order By: Relevance
“…Although we carefully chose isolated commercial orchards for our study, we could not exclude the existence of scattered single host trees, e.g., in backyards of village houses, which could have served as stepping stones for dispersing oriental fruit moths. Grapholita molesta is known as a relatively weak flyer (Yetter & Steiner, ; Hughes & Dorn, ; Sciarretta & Trematerra, ), but it has been shown that both abiotic (Hughes et al., ; Ferrer et al., , ) and biotic environment factors (Pinero & Dorn, ) can stimulate flight, especially in the later part of the season.…”
Section: Discussionmentioning
confidence: 99%
“…Although we carefully chose isolated commercial orchards for our study, we could not exclude the existence of scattered single host trees, e.g., in backyards of village houses, which could have served as stepping stones for dispersing oriental fruit moths. Grapholita molesta is known as a relatively weak flyer (Yetter & Steiner, ; Hughes & Dorn, ; Sciarretta & Trematerra, ), but it has been shown that both abiotic (Hughes et al., ; Ferrer et al., , ) and biotic environment factors (Pinero & Dorn, ) can stimulate flight, especially in the later part of the season.…”
Section: Discussionmentioning
confidence: 99%
“…Tortricid adults readily disperse among both managed agricultural habitats and a variety of surrounding unmanaged host plants (Jeanneret and Charmillot 1995;Knight 2001;Thistlewood and Judd 2003a;Ellis and Hull 2013;Ferrer et al 2014). Urban encroachment into traditional agricultural areas affects the proximity of unmanaged hosts for tortricids impacting orchard management and production, for example homeowners want their own fruit trees but not the added labour of growing their trees to mitigate risks to commercial crops.…”
Section: Area-wide Ipmmentioning
confidence: 99%
“…Insect pests that are most affected by climate change and global warming are those that are ectothermic because they can quickly acclimatize to different environmental conditions. This gives them an advantage to multiply aggressively, increasing their threat to crop production (Ferrer et al, 2014). Examples of insect pests that easily adapt to high temperatures include, aphids, whitefly and stem borers .…”
Section: Climate Variabilitymentioning
confidence: 99%
“…In the UK, the lepidopteran moths and butterflies have been reported each year to have increased in migration rate and this has been linked to increased temperatures in the south west Europe (Sparks et al, 2007). Grapholita molesta (Busck), a lepidopterian moth has the potential to adapt to high temperature environment and has been found to have good flying abilities under high temperature (Ferrer et al, 2014). In Africa, smallholder farmers are most likely to be vulnerable to this factor because severe high temperatures are predicted to be experienced in African areas (Biber-Freudenberger et al, 2016).…”
Section: Impact Of Temperature On Insects and Diseasementioning
confidence: 99%